2001
DOI: 10.1136/jech.55.6.389
|View full text |Cite
|
Sign up to set email alerts
|

Lower use of dental services among long term cigarette smokers

Abstract: Study objective-Given the advanced stage of most oral cancer cases at diagnosis, it is hypothesised that a significant proportion of higher risk adults do not visit a dentist annually. The study objectives were to assess whether long term smokers were less likely to visit the dentist. Design-Data from the 1998 Massachusetts Behavioral Risk Factor Surveillance System, a population-based, random digit dial telephone health survey, were used to evaluate whether adults at higher risk of oral cancer attributable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
3
34
1
Order By: Relevance
“…Also, only one question assessed time of last visit to the dentist, and no specific information about oral health and regular dentist visits was obtained. Previous research suggested that smokers and ex-smokers have received less preventive care than nonsmokers (Mucci & Brooks, 2001), and this may have been true of the smokers in this study. Our data are suggestive of this point, because smokers and ex-smokers had fewer filled teeth and more missing and decayed teeth than nonsmokers, possibly indicating lack of regular dental care.…”
Section: Discussionmentioning
confidence: 74%
“…Also, only one question assessed time of last visit to the dentist, and no specific information about oral health and regular dentist visits was obtained. Previous research suggested that smokers and ex-smokers have received less preventive care than nonsmokers (Mucci & Brooks, 2001), and this may have been true of the smokers in this study. Our data are suggestive of this point, because smokers and ex-smokers had fewer filled teeth and more missing and decayed teeth than nonsmokers, possibly indicating lack of regular dental care.…”
Section: Discussionmentioning
confidence: 74%
“…Smokers may have lifestyle habits that are able to modify their oral health status [34]. Potentially, socio-behavioral factors could contribute more than biological ones to this relationship; as a major risk factor for general and oral health tobacco consumption is strongly related to educational and economic factors, while socio-economic development has been widely associated with caries experience [5].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use could have a role in changes of the bacterial ecology and plaque accumulation [Pihlstrom et al, 2005]. Moreover smokers may have lifestyle habits able to modify their oral health status [Mucci and Brooks, 2001].…”
mentioning
confidence: 99%